Autorepression‐Based Conditional Gene Expression System in Yeast for Variation‐Suppressed Control of Protein Dosage. Issue 1 (28th January 2023) - Azizoğlu, Aslı; Loureiro, Cristina; Venetz, Jonathan; Brent, Roger
Abstract: Conditional control of gene expression allows an experimenter to investigate many aspects of a gene's function. In the model organism Saccharomyces cerevisiae, a number of methods to control gene expression are widely practiced, including induction by metabolites, small molecules, and even light. However, all current methods suffer from at least one of a set of drawbacks, including need for specialized growth conditions, leaky expression, or requirement of specialized equipment. Here we describe protocols using two transformations to construct strains that carry a new controller in which all these drawbacks are overcome. In these strains, the expression of a controlled gene of interest is repressed by the bacterial repressor TetR and induced by anhydrotetracycline. TetR also regulates its own expression, creating an autorepression loop. This autorepression allows tight control of gene expression and protein dosage with low cell‐to‐cell variation in expression. A second repressor, TetR‐Tup1, prevents any leaky expression. We also present a protocol showing a particular workhorse application of such strains to generate synchronized cell populations. We turn off expression of the cell cycle regulator CDC20 completely, arresting the cell population, and then we turn it back on so that the synchronized cells resume cell cycle progression. This control system can be applied to any endogenous or exogenous gene for precise expression. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Generating a parent WTC846 strain Basic Protocol 2 : Generating a WTC846 strain with controlled expression of the targeted gene Alternate Protocol : CRISPR‐mediated promoter replacement Basic Protocol 3 : Cell cycle synchronization/arrest and release using the WTC846‐ K3 ::CDC20 strain